Razredna logika v Kraljevini Jugoslaviji kot periferiji fašističnih sistemov - Centrih, Lev (Teorija in praksa, 2011)
In the light of the historical materialist problematic of social classes and the global division of labour, this article deals with economical and political transformations in the late Kingdom of Yugoslavia (The Banovina of Drava), defining it as a periphery of the European semi-periphery composed of fascist systems. The local and central elites in the Kingdom of Yugoslavia failed to propose a political/economical project strong enough to enable them to practice firm class domination. This is the context in which this article elaborates the social doctrine of political Catholicism in Banovina of Drava, outlining its particular understanding of corporatism as opposed to a superficially similar state-centralist paradigm.
Keywords: Historical materialism; Zgodovinski materializem; Marksistična teorija; Marxist theory; Družbeni razredi; Social classes; Fascism; Fašizem; Jugoslavija; Yugoslavia; marksizem; Marxism; politični katolicizem